2012
DOI: 10.1242/jeb.063297
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine improves learning in newly emerged bees but not in old foragers

Abstract: SUMMARYHoney bees (Apis mellifera) are well known for their excellent learning abilities. Although most age groups learn quickly to associate an odor with a sucrose reward, newly emerged bees and old foragers often perform poorly. For a long time, the reason for the poor learning performance of these age groups was unclear. We show that reduced sensitivity for sucrose is the cause for poor associative learning in newly emerged bees but not in old foragers. By increasing the sensitivity for sucrose through octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 54 publications
2
35
1
Order By: Relevance
“…perception of the sucrose reward in a water solution. Indeed, we could demonstrate that increasing gustatory responsiveness through pharmacological activation of octopamine receptors suffices to improve appetitive learning performance in young bees (Behrends and Scheiner, 2012). Our current results provide further support for the hypothesis that there is a causal relationship between gustatory responsiveness and appetitive PER learning in honeybees by ) into the hemolymph (tyramine titer: n control =9, n tyramine =7, octopamine titer: n control =10, n tyramine =7).…”
Section: Discussion Social Role Gustatory Responsiveness and Appetitsupporting
confidence: 80%
See 3 more Smart Citations
“…perception of the sucrose reward in a water solution. Indeed, we could demonstrate that increasing gustatory responsiveness through pharmacological activation of octopamine receptors suffices to improve appetitive learning performance in young bees (Behrends and Scheiner, 2012). Our current results provide further support for the hypothesis that there is a causal relationship between gustatory responsiveness and appetitive PER learning in honeybees by ) into the hemolymph (tyramine titer: n control =9, n tyramine =7, octopamine titer: n control =10, n tyramine =7).…”
Section: Discussion Social Role Gustatory Responsiveness and Appetitsupporting
confidence: 80%
“…The behavioral changes of tyramine that are similar to those of octopamine might be achieved through the second honeybee tyramine receptor, AmTYR2, which acts similarly to the octopamine receptors AmOCTβR1 to AMOCTβR4 (Balfanz et al, 2014;Reim et al, 2017) by upregulating cAMP. Octopamine similarly improves appetitive learning performance in honeybees, as does tyramine (Behrends and Scheiner, 2012). However, these are pure speculations.…”
Section: Function Of Tyramine Receptors In Gustatory Responsiveness Amentioning
confidence: 96%
See 2 more Smart Citations
“…For the honeybee, several studies showed that factors such as satiation level, behavioral role or age have an effect on individual responsiveness for sucrose, which in turn affects learning performance (Scheiner et al, 1999; Friedrich et al, 2004; Behrends and Scheiner, 2012). Re-analyzing data in which the responsiveness to sucrose was estimated prior to conditioning we studied the correlation between this experimental measure and the individual learning dynamics.…”
Section: Introductionmentioning
confidence: 99%